Rola powtórzeń w "Civilisation universelle et cultures nationales" Paula Ricœura - Bobowska-Nastarzewska, Patrycja (Acta Neophilologica, 2021)
This paper concerns the role of repetitions in Paul Ricoeur’s text entitled Universal Civilization and National Cultures (1961). The analysis aims to prove that the repetitions are a characteristic element of the philosopher’s style. In the analysis the author focuses on the repetitions in the connected and disconnected word order and on repetitions as figures of speech. Ricoeur repeats in his text words, expressions and grammatical constructions. A distinctive element of Ricoeur’s style is also the text structure, e.g., the text division into three parts, the so-called triad system.